Декомпозиция и композиция свойств альтернатив в многокритериальных задачах принятия решений - Воронин, А.Н. (Кибернетика и системный анализ, 2009)
Показано, що при векторному підході задача прийняття рішень шляхом декомпозиції властивостей альтернатив репрезентується ієрархічною системою критеріїв. На нижчому рівні ієрархії здійснюється оцінка альтернативи за окремими властивостями за допомогою вектора критеріїв, а на верхньому рівні шляхом застосування механізму композиції отримується оцінка альтернативи у цілому. Задача розв’язується методом вкладених скалярних згорток. It is shown that, in the vector approach, the problem of making decisions by decomposing properties of alternatives is represented by a hierarchical system of criteria. At the lower hierarchy level, an alternative is estimated from separate properties on the basis of a vector of criteria and, at the upper level, a composition mechanism is used to estimate the alternative as a whole. The problem is solved by the method of nested scalar convolutions of vector-valued criteria.